Pengungkapan Sustainability Report dalam Meningkatkan Kinerja Perusahaan: Peran Ukuran Perusahaan sebagai Moderasi - Meidiyustiani, Rinny; Rachmat Arief (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Sustainable reporting, or sustainable accounting, is gaining traction as a tool to mitigate the environmental and social impacts faced by companies, while maintaining healthy financial performance. This study aims to find out whether there is an effect of the disclosure of the Sustainability Report on the company's performance with company size as a moderation variable. This type of research is quantitative research. The source of data for this research uses secondary data obtained from the company's financial statements published on the Indonesia Stock Exchange (IDX) and also uses sustainability reports (Sustainability Report) obtained from the company's official website and on the Indonesia Stock Exchange (IDX). The data was analyzed using the SPSS 26 program. Sampling in this study uses the purposive sampling method. The sample used is food and beverage companies that meet the criteria. conducted in this study using a moderation regression test with an SPSS test tool. The hypothesis test based on the t-test showed that there was no significant influence between economic dimension variables on company performance variables. As for the environmental dimension and the social dimension, it is concluded that these dimensions each affect financial performance. The company size variable is able to moderate the influence of the relationship between the environmental dimension and the social dimension on the company's performance and the company size variable is not able to moderate the influence of the economic dimension relationship on the company's performance.